Antibacterial silk fabric and preparation method thereof

By reacting the silk with DL-Acelatal-3-phosphate, 3-hydroxypin pyrrole, and silver acetate, silver silk is carried out, and the antibacterial silk fabric is made with daily ammonium altering calcium carbonate? Silk fabrics are easy to breed bacteria and mold problems, realize efficient antibacterial and flame retardant effects, and have good anti -static performance.

CN119352181APending Publication Date: 2025-01-24JIANGSU BEIBAO SILK PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411572689.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Silk fibers are prone to bacterial growth and degradation by mold, causing discoloration, deformation and mold to occur in silk, which cannot effectively solve the antibacterial and flame retardant problems of silk fabrics.

Method used

By reacting the dehydrated silk-3-phosphate, 3-hydroxyl pyrrole, and silver acetate in order to make silver silk, and sodium bicarbonate is loaded on the ductional alama calcium carbonate crystal The reaction is made of a compound silk, and finally reacted with Pilar, and then static spinning and weaving to make antibacterial silk fabrics.

Benefits of technology

It improves the antibacterial and flame retardant capabilities of silk fabrics, extends the service life of silk, enhances its resistance to bacteria and mold, and has good antistatic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005120912220000121
    Figure BDA0005120912220000121
Patent Text Reader

Abstract

The invention discloses an antibacterial silk fabric and a preparation method thereof, and relates to the field of textile fabrics. When the antibacterial silk fabric is prepared, degummed silk sequentially reacts with DL-glyceraldehyde-3-phosphoric acid, 3-hydroxypyrrole and silver acetate to prepare silver-loaded silk; trimethoxysilane is subjected to a reaction with dimethylallylamine, the modified calcium carbonate whiskers and dibromoethane in sequence, and quaternization modified calcium carbonate whiskers are prepared; loading sodium bicarbonate on the surface of the quaternized modified calcium carbonate whisker, and reacting with the silver-loaded silk to obtain composite silk; the composite silk reacts with pyrrole, electrostatic spinning and weaving are conducted, and the antibacterial silk fabric is obtained. The antibacterial silk fabric prepared by the invention has flame-retardant and antistatic capabilities.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of textile fabrics, in particular to an antibacterial silk fabric and a preparation method thereof. Background Art

[0002] Silk is a natural long continuous fiber of animal protein, formed by the solidification of silk fluid secreted by mature silkworms when they make cocoons. It is also called natural silk. As early as more than 5,000 years ago, it is said that Leizu, the wife of Emperor Huangdi, began to teach people to raise silkworms. During the Shang and Zhou dynasties, the Chinese nation had begun to use silk to weave silk fabrics such as gauze, damask, crepe, gauze, brocade, embroidery, etc., and exported them overseas. It became a luxury product dreamed of by Western aristocrats. Therefore, there was the "Silk Road". To this day, silk products are still high-end products in people's lives. For thousands of years, silk and silk culture have been deeply integrated into the lives of the Chinese people, affecting the Chinese people's value orientation, way of thinking and cultural cognition. It is the most precious cultural heritage of the Chinese nation.

[0003] With the development of modern society, the awareness of environmental protection has been strengthened. The pollution of the environment in the production process of artificial fibers has attracted great attention from the society. Market consumers are increasingly advocating comfortable, healthy, beautiful and green textiles. Silk is pollution-free from mulberry planting and silkworm breeding to silk-making process, so natural silk products are becoming more and more popular among consumers. However, silk products also have some disadvantages in the use process. For example, silk is composed of animal protein and there will be many micropores when the fibers are stacked and woven, which makes silk fibers easy to breed bacteria and be degraded by mold. Bacteria and mold will secrete protease to decompose protein into the nutrients they need, causing silk to discolor, deform and rot. Therefore, this article introduces an antibacterial silk fabric with flame retardant and antistatic capabilities. Summary of the invention

[0004] The purpose of the present invention is to provide an antibacterial silk fabric and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] The invention discloses an antibacterial silk fabric, which is prepared by reacting composite silk with pyrrole, and then electrostatically spinning and weaving.

[0006] As an optimization, the composite silk is prepared by loading sodium bicarbonate on the surface of quaternary ammonium modified calcium carbonate whiskers and then reacting with silver-loaded silk.

[0007] As an optimization, the silver-loaded silk is prepared by reacting degummed silk with DL-glyceraldehyde-3-phosphate, 3-hydroxypyrrole and silver acetate in sequence.

[0008] As an optimization, the quaternized modified calcium carbonate whisker is prepared by sequentially reacting trimethoxysilane with dimethylallylamine, modified calcium carbonate whisker and dibromoethane.

[0009] A method for preparing an antibacterial silk fabric, the method for preparing the antibacterial silk fabric mainly comprises the following preparation steps:

[0010] (1) adding the degummed silk dispersion to a DL-glyceraldehyde-3-phosphate solution of 0.3 to 0.5 times the mass of the degummed silk dispersion at a uniform speed within 8 to 10 minutes, stirring at 200 to 240 r / min for 100 to 140 minutes, filtering, washing with ethanol for 3 to 5 times, and vacuum drying at -10 to -1°C for 22 to 24 hours to obtain pre-modified silk;

[0011] (2) Pre-modified silk, urea and deionized water are mixed in a mass ratio of 1:2-5:5-7, stirred at 70-80°C and 200-300 r / min for 8-10 min, heated to 80-100°C, and stirred continuously. 3-hydroxypyrrole in an amount of 0.05-0.08 times the mass of the pre-modified silk is added at a uniform rate within 50-70 min, reacted at 94-96°C for 2.5-3.5 h, and deionized water in an amount of 3-5 times the mass is added. The modified silk was prepared by mixing the modified silk, silver acetate and deionized water in a mass ratio of 1:0.5-0.7:3-5, stirring at 150-170°C and 200-300 r / min for 8-10 min, taking out, and vacuum drying at 40-60°C for 8-12 h to obtain silver-loaded silk.

[0012] (3) trimethoxysilane and dimethylallylamine are mixed in a molar ratio of 1:1, chloroplatinic acid is added in an amount of 0.03 to 0.05 times the mass of trimethoxysilane, and the mixture is reacted at 60 to 70°C for 4 to 6 hours to obtain nitrogen-containing siloxane; calcium carbonate whiskers, nitrogen-containing siloxane and isopropanol are uniformly mixed in a mass ratio of 15 to 25:1:30 to 50, stirred at 85 to 95°C and 200 to 300 r / min for 5 to 7 hours, the solid is centrifuged, washed with deionized water for 3 to 5 times, and dried at 90 to 100°C for 2 to 4 hours to obtain modified calcium carbonate whiskers;

[0013] (4) Modified calcium carbonate whiskers, ethylene dibromide, ethanol and deionized water are mixed in a mass ratio of 2 to 4:1:

[0014] 1.5-2.5:7-9, stirring at 80-90°C and 200-300r / min for 5-7h, filtering, washing with ethanol for 3-5 times, drying at 50-60°C for 5-7h, to obtain quaternary ammonium modified calcium carbonate whiskers; soaking the quaternary ammonium calcium carbonate whiskers in a saturated sodium bicarbonate solution for 30-45s, taking out, drying at 50-60°C for 12-14h, to obtain foaming agent-loaded calcium carbonate whiskers;

[0015] (5) Calcium carbonate whiskers carrying a foaming agent, silver-carrying silk, sodium hydride and deionized water are mixed in a mass ratio of 1:8-10:0.08-0.12:30-40, stirred at 90-110°C and 200-300 r / min for 8-12 hours, filtered, and washed with deionized water for 3-5 times to obtain composite silk; pyrrole, ethanol and deionized water are mixed in a mass ratio of 5-7:1-3:7-9, stirred at 200-300 r / min for 8-10 minutes, 0.03-0.05 times the mass of pyrrole ferric chloride is added, and stirring is continued for 20-40 seconds to obtain a pyrrole mixed solution; the composite silk is immersed in the pyrrole mixed solution for 30-50 seconds, taken out, and dried at 40-60°C for 22-26 hours to obtain modified composite silk, and the modified composite silk is electrostatically spun and woven to obtain antibacterial silk fabrics.

[0016] As an optimization, the degummed silk in step (1) is prepared by immersing the silk in a sodium carbonate solution having a mass fraction of 0.04% to 0.06% and boiling it for 20 to 40 minutes, taking it out, washing it with deionized water for 3 to 5 times, and then boiling it with deionized water for 20 to 40 minutes, repeating the above steps 2 to 4 times, taking out the silk, and drying it at room temperature for 20 to 24 hours.

[0017] As an optimization, the degummed silk dispersion in step (1) is prepared by uniformly mixing the degummed silk and anhydrous ethanol in a mass ratio of 1:1.

[0018] As an optimization, the DL-glyceraldehyde-3-phosphate solution in step (1) is prepared by uniformly mixing DL-glyceraldehyde-3-phosphate and anhydrous ethanol in a mass ratio of 1:1.

[0019] As an optimization, the electrospinning method in step (5) is to uniformly mix the modified composite silk and hexafluoroisopropanol at a mass ratio of 1:10 to obtain an electrospinning solution; and to spin the electrospinning solution at a spinning flow rate of 1.4 to 1.6 ml / h, a spinning voltage of 14 to 16 KV, a receiving distance of 14 to 16 cm, and a collector speed of 250 to 350 r / min.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] When preparing the antibacterial silk fabric, the present invention comprises the following steps: reacting the degummed silk with DL-glyceraldehyde-3-phosphate, 3-hydroxypyrrole and silver acetate in sequence to obtain the silver-loaded silk; reacting trimethoxysilane with dimethylallylamine, modified calcium carbonate whisker and dibromoethane in sequence to obtain the quaternized modified calcium carbonate whisker; loading sodium bicarbonate on the surface of the quaternized modified calcium carbonate whisker and reacting the sodium bicarbonate with the silver-loaded silk to obtain the composite silk; reacting the composite silk with pyrrole, and then electrostatic spinning and weaving to obtain the antibacterial silk fabric.

[0022] Firstly, when preparing the antibacterial silk fabric, the present invention sequentially reacts the degummed silk with DL-glyceraldehyde-3-phosphate, 3-hydroxypyrrole and silver acetate to obtain the silver-loaded silk; the organic phosphorus can generate phosphorus-containing free radicals, which can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction to slow down the combustion, and can generate polymetaphosphoric acid with stable structure and low volatility during the combustion process; the polymetaphosphoric acid has a strong dehydration effect, and promotes the carbonization of the polymer into a dense and flame-retardant carbonized layer during the heating process; the carbonized layer covers the surface of the polymer, and isolates the bottom material from the external oxygen. Contact and hinder the transfer of external heat to the base material, thereby effectively preventing the further pyrolysis of the material and then terminating the combustion of the material, and improving the flame retardant ability of the material; the degummed silk reacts with DL-glyceraldehyde-3-phosphate to produce a large amount of Schiff base, which can form Schiff base silver ligands with silver acetate. The Schiff base ligands can combine with the negative charge of the microbial biofilm to rupture the biofilm, and the silver ligands can slowly release silver ions to react with the thiol, amino, hydroxyl and other functional groups on the protein, thereby destroying the growth and reproduction of microorganisms and achieving an antibacterial effect.

[0023] Secondly, trimethoxysilane is reacted with dimethylallylamine, modified calcium carbonate whiskers and dibromoethane in sequence to obtain quaternary ammonium modified calcium carbonate whiskers; sodium bicarbonate is loaded on the surface of quaternary ammonium modified calcium carbonate whiskers and then reacted with silver-loaded silk to obtain composite silk; the composite silk is reacted with pyrrole, and then electrospun and woven to obtain antibacterial silk fabrics; quaternary ammonium salts can destroy the cell membrane structure and promote bacterial death, thereby achieving an antibacterial effect; quaternary ammonium modified calcium carbonate whiskers can better combine with the bicarbonate ion of sodium bicarbonate, When reacting with silver-loaded silk, sodium bicarbonate will produce a large number of bubbles, making the resulting material rich in pores, which is convenient for the subsequent synthesis of polypyrrole; polypyrrole can decompose to produce non-flammable gas after absorbing heat, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of the polymer on the one hand, and on the other hand, the nitrogen oxides produced by the decomposition can capture free radicals, inhibit the chain reaction of the polymer, and improve the flame retardant ability of the material; polypyrrole, as a conductive polymer, can improve the antistatic ability of the material, and polypyrrole also has a partial antibacterial effect. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A method for preparing an antibacterial silk fabric mainly comprises the following preparation steps:

[0027] (1) adding the degummed silk dispersion into a DL-glyceraldehyde-3-phosphate solution with a mass of 0.3 times that of the degummed silk dispersion at a uniform speed within 8 minutes, stirring at 200 r / min for 100 minutes, filtering, washing with ethanol for 3 times, and vacuum drying at -10°C for 22 hours to obtain pre-modified silk;

[0028] (2) Pre-modified silk, urea and deionized water were mixed in a mass ratio of 1:2:5, stirred at 70°C and 200 r / min for 8 min, heated to 80°C, continued to stir, and added 3-hydroxypyrrole at a uniform rate of 0.05 times the mass of the pre-modified silk within 50 min, reacted at 94°C for 2.5 h, poured into ethanol 3 times the mass of deionized water, allowed to stand for 2 h, filtered, washed with deionized water until the pH reached 5, and vacuum dried at 40°C for 8 h to obtain modified silk; modified silk, silver acetate and deionized water were mixed in a mass ratio of 1:0.5:3, stirred at 150°C and 200 r / min for 8 min, taken out, and vacuum dried at 40°C for 8 h to obtain silver-loaded silk;

[0029] (3) trimethoxysilane and dimethylallylamine were mixed in a molar ratio of 1:1, chloroplatinic acid was added in an amount of 0.03 times the mass of trimethoxysilane, and the mixture was reacted at 60°C for 4 hours to obtain nitrogen-containing siloxane; calcium carbonate whiskers, nitrogen-containing siloxane and isopropanol were mixed in a mass ratio of 15:1:30, stirred at 85°C and 200 r / min for 5 hours, and the solid was separated by centrifugation, washed with deionized water for 3 times, and dried at 90°C for 2 hours to obtain modified calcium carbonate whiskers;

[0030] (4) Modified calcium carbonate whiskers, dibromoethane, ethanol and deionized water were mixed in a mass ratio of 2:1:1.5:7, stirred at 80°C and 200 r / min for 5 hours, filtered, washed with ethanol three times, and dried at 50°C for 5 hours to obtain quaternized modified calcium carbonate whiskers; the quaternized calcium carbonate whiskers were immersed in a saturated sodium bicarbonate solution for 30 seconds, taken out, and dried at 50°C for 12 hours to obtain foaming agent-loaded calcium carbonate whiskers;

[0031] (5) Calcium carbonate whiskers loaded with foaming agent, silver-loaded silk, sodium hydride and deionized water were mixed in a mass ratio of 1:8:0.08:30, stirred at 90°C and 200 r / min for 8 h, filtered, and washed with deionized water for 3 times to obtain composite silk; pyrrole, ethanol and deionized water were mixed in a mass ratio of 5:1:7, stirred at 200 r / min for 8 min, 0.03 times the mass of pyrrole ferric chloride was added, and stirring was continued for 20 s to obtain a pyrrole mixed solution; the composite silk was immersed in the pyrrole mixed solution for 30 s, taken out, and dried at 40°C for 22 h to obtain modified composite silk, and the modified composite silk was electrospun and woven to obtain antibacterial silk fabrics.

[0032] Example 2

[0033] A method for preparing an antibacterial silk fabric mainly comprises the following preparation steps:

[0034] (1) adding the degummed silk dispersion to a DL-glyceraldehyde-3-phosphate solution with a mass of 0.4 times that of the degummed silk dispersion at a uniform speed within 9 minutes, stirring at 220 r / min for 120 minutes, filtering, washing with ethanol for 4 times, and vacuum drying at -5.5°C for 23 hours to obtain pre-modified silk;

[0035] (2) Pre-modified silk, urea and deionized water were mixed in a mass ratio of 1:3.5:6, stirred at 75°C and 250 r / min for 9 minutes, heated to 90°C, and continued to stir, and 3-hydroxypyrrole (0.065 times the mass of the pre-modified silk) was added at a uniform rate within 60 minutes, reacted at 95°C for 3 hours, poured into ethanol (4 times the mass of deionized water), allowed to stand for 3 hours, filtered, washed with deionized water until the pH reached 5.5, and vacuum dried at 50°C for 10 hours to obtain modified silk; modified silk, silver acetate and deionized water were mixed in a mass ratio of 1:0.6:4, stirred at 160°C and 250 r / min for 9 minutes, taken out, and vacuum dried at 50°C for 10 hours to obtain silver-loaded silk;

[0036] (3) trimethoxysilane and dimethylallylamine were mixed in a molar ratio of 1:1, chloroplatinic acid was added in an amount of 0.04 times the mass of trimethoxysilane, and the mixture was reacted at 65°C for 5 hours to obtain nitrogen-containing siloxane; calcium carbonate whiskers, nitrogen-containing siloxane and isopropanol were mixed in a mass ratio of 20:1:40, stirred at 90°C and 250 r / min for 6 hours, the solid was separated by centrifugation, washed with deionized water for 4 times, and dried at 95°C for 3 hours to obtain modified calcium carbonate whiskers;

[0037] (4) Modified calcium carbonate whiskers, dibromoethane, ethanol and deionized water were mixed in a mass ratio of 3:1:2:8, stirred at 85°C and 250 r / min for 6 hours, filtered, washed with ethanol 4 times, and dried at 55°C for 6 hours to obtain quaternized modified calcium carbonate whiskers; the quaternized calcium carbonate whiskers were immersed in a saturated sodium bicarbonate solution for 37.5 seconds, taken out, and dried at 55°C for 13 hours to obtain foaming agent-loaded calcium carbonate whiskers;

[0038] (5) Calcium carbonate whiskers loaded with foaming agent, silver-loaded silk, sodium hydride and deionized water were mixed in a mass ratio of 1:9:0.1:35, stirred at 100°C and 250 r / min for 10 h, filtered, and washed with deionized water for 4 times to obtain composite silk; pyrrole, ethanol and deionized water were mixed in a mass ratio of 6:2:8, stirred at 250 r / min for 9 min, 0.04 times the mass of pyrrole ferric chloride was added, and stirring was continued for 30 s to obtain a pyrrole mixed solution; the composite silk was immersed in the pyrrole mixed solution for 40 s, taken out, and dried at 50°C for 24 h to obtain modified composite silk, and the modified composite silk was electrospun and woven to obtain antibacterial silk fabric.

[0039] Example 3

[0040] A method for preparing an antibacterial silk fabric mainly comprises the following preparation steps:

[0041] (1) adding the degummed silk dispersion to a DL-glyceraldehyde-3-phosphate solution with a mass of 0.5 times that of the degummed silk dispersion at a uniform speed within 10 minutes, stirring at 240 r / min for 140 minutes, filtering, washing with ethanol for 5 times, and vacuum drying at -1°C for 24 hours to obtain pre-modified silk;

[0042] (2) Pre-modified silk, urea and deionized water were mixed in a mass ratio of 1:5:7, stirred at 80°C and 300 r / min for 10 min, heated to 100°C, and continued to stir, and 0.08 times the mass of pre-modified silk 3-hydroxypyrrole was uniformly added within 70 min, reacted at 96°C for 3.5 h, poured into ethanol 5 times the mass of deionized water, allowed to stand for 4 h, filtered, washed with deionized water until the pH reached 6, and vacuum dried at 60°C for 12 h to obtain modified silk; modified silk, silver acetate and deionized water were mixed in a mass ratio of 1:0.7:5, stirred at 170°C and 300 r / min for 10 min, taken out, and vacuum dried at 60°C for 12 h to obtain silver-loaded silk;

[0043] (3) trimethoxysilane and dimethylallylamine were mixed in a molar ratio of 1:1, chloroplatinic acid was added in an amount of 0.05 times the mass of trimethoxysilane, and the mixture was reacted at 70°C for 6 hours to obtain nitrogen-containing siloxane; calcium carbonate whiskers, nitrogen-containing siloxane and isopropanol were mixed in a mass ratio of 25:1:50, stirred at 95°C and 300 r / min for 7 hours, the solid was separated by centrifugation, washed with deionized water for 5 times, and dried at 100°C for 4 hours to obtain modified calcium carbonate whiskers;

[0044] (4) Modified calcium carbonate whiskers, dibromoethane, ethanol and deionized water were mixed in a mass ratio of 4:1:2.5:9, stirred at 90°C and 300 r / min for 7 hours, filtered, washed with ethanol 5 times, and dried at 60°C for 7 hours to obtain quaternized modified calcium carbonate whiskers; the quaternized calcium carbonate whiskers were immersed in a saturated sodium bicarbonate solution for 45 seconds, taken out, and dried at 60°C for 14 hours to obtain foaming agent-loaded calcium carbonate whiskers;

[0045] (5) Calcium carbonate whiskers loaded with foaming agent, silver-loaded silk, sodium hydride and deionized water were mixed in a mass ratio of 1:10:0.12:40, stirred at 110°C and 300 r / min for 12 h, filtered, and washed with deionized water for 5 times to obtain composite silk; pyrrole, ethanol and deionized water were mixed in a mass ratio of 7:3:9, stirred at 300 r / min for 10 min, 0.05 times the mass of pyrrole ferric chloride was added, and stirring was continued for 40 s to obtain a pyrrole mixed solution; the composite silk was immersed in the pyrrole mixed solution for 50 s, taken out, and dried at 60°C for 26 h to obtain modified composite silk, and the modified composite silk was electrospun and woven to obtain antibacterial silk fabric.

[0046] Comparative Example 1

[0047] A method for preparing an antibacterial silk fabric mainly comprises the following preparation steps:

[0048] (1) adding the degummed silk dispersion into a pyrrole-3-carboxaldehyde solution with a mass 0.4 times that of the degummed silk dispersion at a uniform speed within 9 minutes, stirring at 220 r / min for 120 minutes, filtering, washing with ethanol for 4 times, and vacuum drying at -5.5°C for 23 hours to obtain pre-modified silk;

[0049] (2) pre-modified silk, silver acetate and deionized water were mixed in a mass ratio of 1:0.6:4, stirred at 160°C and 250 r / min for 9 min, taken out, and vacuum dried at 50°C for 10 h to obtain silver-loaded silk;

[0050] (3) trimethoxysilane and dimethylallylamine were mixed in a molar ratio of 1:1, chloroplatinic acid was added in an amount of 0.04 times the mass of trimethoxysilane, and the mixture was reacted at 65°C for 5 hours to obtain nitrogen-containing siloxane; calcium carbonate whiskers, nitrogen-containing siloxane and isopropanol were mixed in a mass ratio of 20:1:40, stirred at 90°C and 250 r / min for 6 hours, the solid was separated by centrifugation, washed with deionized water for 4 times, and dried at 95°C for 3 hours to obtain modified calcium carbonate whiskers;

[0051] (4) Modified calcium carbonate whiskers, dibromoethane, ethanol and deionized water were mixed in a mass ratio of 3:1:2:8, stirred at 85°C and 250 r / min for 6 hours, filtered, washed with ethanol 4 times, and dried at 55°C for 6 hours to obtain quaternized modified calcium carbonate whiskers; the quaternized calcium carbonate whiskers were immersed in a saturated sodium bicarbonate solution for 37.5 seconds, taken out, and dried at 55°C for 13 hours to obtain foaming agent-loaded calcium carbonate whiskers;

[0052] (5) Calcium carbonate whiskers loaded with foaming agent, silver-loaded silk, sodium hydride and deionized water were mixed in a mass ratio of 1:9:0.1:35, stirred at 100°C and 250 r / min for 10 h, filtered, and washed with deionized water for 4 times to obtain composite silk; pyrrole, ethanol and deionized water were mixed in a mass ratio of 6:2:8, stirred at 250 r / min for 9 min, 0.04 times the mass of pyrrole ferric chloride was added, and stirring was continued for 30 s to obtain a pyrrole mixed solution; the composite silk was immersed in the pyrrole mixed solution for 40 s, taken out, and dried at 50°C for 24 h to obtain modified composite silk, and the modified composite silk was electrospun and woven to obtain antibacterial silk fabric.

[0053] Comparative Example 2

[0054] A method for preparing an antibacterial silk fabric mainly comprises the following preparation steps:

[0055] (1) adding the degummed silk dispersion to a DL-glyceraldehyde-3-phosphate solution with a mass of 0.4 times that of the degummed silk dispersion at a uniform speed within 9 minutes, stirring at 220 r / min for 120 minutes, filtering, washing with ethanol for 4 times, and vacuum drying at -5.5°C for 23 hours to obtain pre-modified silk;

[0056] (2) Pre-modified silk, urea and deionized water were mixed in a mass ratio of 1:3.5:6, stirred at 75°C and 250 r / min for 9 min, heated to 90°C, and continued to stir. 3-hydroxypyrrole (0.065 times the mass of the pre-modified silk) was added at a uniform rate within 60 min, reacted at 95°C for 3 h, poured into ethanol (4 times the mass of deionized water), allowed to stand for 3 h, filtered, washed with deionized water until the pH reached 5.5, and vacuum dried at 50°C for 10 h to obtain modified silk;

[0057] (3) trimethoxysilane and dimethylallylamine were mixed in a molar ratio of 1:1, chloroplatinic acid was added in an amount of 0.04 times the mass of trimethoxysilane, and the mixture was reacted at 65°C for 5 hours to obtain nitrogen-containing siloxane; calcium carbonate whiskers, nitrogen-containing siloxane and isopropanol were mixed in a mass ratio of 20:1:40, stirred at 90°C and 250 r / min for 6 hours, the solid was separated by centrifugation, washed with deionized water for 4 times, and dried at 95°C for 3 hours to obtain modified calcium carbonate whiskers;

[0058] (4) Modified calcium carbonate whiskers, dibromoethane, ethanol and deionized water were mixed in a mass ratio of 3:1:2:8, stirred at 85°C and 250 r / min for 6 hours, filtered, washed with ethanol 4 times, and dried at 55°C for 6 hours to obtain quaternized modified calcium carbonate whiskers; the quaternized calcium carbonate whiskers were immersed in a saturated sodium bicarbonate solution for 37.5 seconds, taken out, and dried at 55°C for 13 hours to obtain foaming agent-loaded calcium carbonate whiskers;

[0059] (5) Calcium carbonate whiskers as a foaming agent, modified silk, sodium hydride and deionized water were mixed in a mass ratio of 1:9:0.1:35, stirred at 100°C and 250 r / min for 10 h, filtered, and washed with deionized water for 4 times to obtain composite silk; pyrrole, ethanol and deionized water were mixed in a mass ratio of 6:2:8, stirred at 250 r / min for 9 min, 0.04 times the mass of pyrrole ferric chloride was added, and stirring was continued for 30 s to obtain a pyrrole mixed solution; the composite silk was immersed in the pyrrole mixed solution for 40 s, taken out, and dried at 50°C for 24 h to obtain modified composite silk, and the modified composite silk was electrospun and woven to obtain antibacterial silk fabrics.

[0060] Comparative Example 3

[0061] A method for preparing an antibacterial silk fabric mainly comprises the following preparation steps:

[0062] (1) adding the degummed silk dispersion to a DL-glyceraldehyde-3-phosphate solution with a mass of 0.4 times that of the degummed silk dispersion at a uniform speed within 9 minutes, stirring at 220 r / min for 120 minutes, filtering, washing with ethanol for 4 times, and vacuum drying at -5.5°C for 23 hours to obtain pre-modified silk;

[0063] (2) Pre-modified silk, urea and deionized water were mixed in a mass ratio of 1:3.5:6, stirred at 75°C and 250 r / min for 9 minutes, heated to 90°C, and continued to stir, and 3-hydroxypyrrole (0.065 times the mass of the pre-modified silk) was added at a uniform rate within 60 minutes, reacted at 95°C for 3 hours, poured into ethanol (4 times the mass of deionized water), allowed to stand for 3 hours, filtered, washed with deionized water until the pH reached 5.5, and vacuum dried at 50°C for 10 hours to obtain modified silk; modified silk, silver acetate and deionized water were mixed in a mass ratio of 1:0.6:4, stirred at 160°C and 250 r / min for 9 minutes, taken out, and vacuum dried at 50°C for 10 hours to obtain silver-loaded silk;

[0064] (3) Calcium carbonate whiskers, silver-loaded silk, sodium hydride and deionized water were mixed in a mass ratio of 1:9:0.1:35, stirred at 100°C and 250 r / min for 10 h, filtered, and washed with deionized water for 4 times to obtain composite silk; pyrrole, ethanol and deionized water were mixed in a mass ratio of 6:2:8, stirred at 250 r / min for 9 min, 0.04 times the mass of pyrrole ferric chloride was added, and stirring was continued for 30 s to obtain a pyrrole mixed solution; the composite silk was immersed in the pyrrole mixed solution for 40 s, taken out, and dried at 50°C for 24 h to obtain modified composite silk, and the modified composite silk was electrospun and woven to obtain antibacterial silk fabrics.

[0065] Comparative Example 4

[0066] A method for preparing an antibacterial silk fabric mainly comprises the following preparation steps:

[0067] (1) adding the degummed silk dispersion to a DL-glyceraldehyde-3-phosphate solution with a mass of 0.4 times that of the degummed silk dispersion at a uniform speed within 9 minutes, stirring at 220 r / min for 120 minutes, filtering, washing with ethanol for 4 times, and vacuum drying at -5.5°C for 23 hours to obtain pre-modified silk;

[0068] (2) Pre-modified silk, urea and deionized water were mixed in a mass ratio of 1:3.5:6, stirred at 75°C and 250 r / min for 9 minutes, heated to 90°C, and continued to stir, and 3-hydroxypyrrole (0.065 times the mass of the pre-modified silk) was added at a uniform rate within 60 minutes, reacted at 95°C for 3 hours, poured into ethanol (4 times the mass of deionized water), allowed to stand for 3 hours, filtered, washed with deionized water until the pH reached 5.5, and vacuum dried at 50°C for 10 hours to obtain modified silk; modified silk, silver acetate and deionized water were mixed in a mass ratio of 1:0.6:4, stirred at 160°C and 250 r / min for 9 minutes, taken out, and vacuum dried at 50°C for 10 hours to obtain silver-loaded silk;

[0069] (3) trimethoxysilane and dimethylallylamine were mixed in a molar ratio of 1:1, chloroplatinic acid was added in an amount of 0.04 times the mass of trimethoxysilane, and the mixture was reacted at 65°C for 5 hours to obtain nitrogen-containing siloxane; calcium carbonate whiskers, nitrogen-containing siloxane and isopropanol were mixed in a mass ratio of 20:1:40, stirred at 90°C and 250 r / min for 6 hours, the solid was separated by centrifugation, washed with deionized water for 4 times, and dried at 95°C for 3 hours to obtain modified calcium carbonate whiskers;

[0070] (4) Modified calcium carbonate whiskers, dibromoethane, ethanol and deionized water were mixed in a mass ratio of 3:1:2:8, stirred at 85°C and 250 r / min for 6 hours, filtered, washed with ethanol 4 times, and dried at 55°C for 6 hours to obtain quaternized modified calcium carbonate whiskers; the quaternized calcium carbonate whiskers were immersed in a saturated sodium bicarbonate solution for 37.5 seconds, taken out, and dried at 55°C for 13 hours to obtain foaming agent-loaded calcium carbonate whiskers;

[0071] (5) Calcium carbonate whiskers carrying a foaming agent, silver-loaded silk, sodium hydride and deionized water are mixed in a mass ratio of 1:9:0.1:35, stirred at 100°C and 250 r / min for 10 h, filtered, and washed with deionized water for 4 times to obtain composite silk; the composite silk is electrostatically spun and woven to obtain antibacterial silk fabrics.

[0072] Test Example 1

[0073] Flame retardancy test

[0074] The limiting oxygen index was tested according to GBT / 2406 test standard. The results are shown in Table 1.

[0075] Table 1

[0076] Limiting oxygen index Example 1 33.8% Example 2 34.4% Example 3 34.0% Comparative Example 1 28.1% Comparative Example 2 34.1% Comparative Example 3 33.6% Comparative Example 4 28.6%

[0077] From the comparison of the experimental data in Table 1, it can be found that the antibacterial silk fabric prepared by the present invention has good flame retardancy.

[0078] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, and 3 is larger than that of Comparative Example 1, which shows that the phosphate ester can generate phosphorus-containing free radicals, can capture hydrogen free radicals and hydroxyl free radicals in the flame area, interrupt the polymer combustion chain reaction to slow down the combustion, and can generate polymetaphosphoric acid with stable structure and non-volatile in the combustion process. Polymetaphosphoric acid has a strong dehydration effect, and promotes the carbonization of the polymer into a dense and flame-retardant carbonized layer during the heating process. The carbonized layer covers the surface of the polymer, isolates the bottom material from the contact with the external oxygen, and hinders the external heat from being transferred to the base material, thereby effectively preventing the material from further pyrolysis and terminating the combustion of the material, improving the flame retardancy of the material, and increasing the limiting oxygen index of the material;

[0079] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 4, which shows that polypyrrole can decompose to produce non-combustible gas after absorbing heat, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of polymers on the one hand, and the nitrogen oxides produced by decomposition can capture free radicals on the other hand, inhibit the chain reaction of polymers, improve the flame retardancy of materials, and increase the limiting oxygen index of materials.

[0080] Test Example 2

[0081] Antimicrobial testing

[0082] The test was carried out according to the GB / T20944 oscillation method, wherein the selected bacteria species were Staphylococcus aureus and Escherichia coli. The results are shown in Table 2.

[0083] Table 2

[0084]

[0085] From the comparison of the experimental data in Table 2, it can be found that the antibacterial silk fabric prepared by the present invention has good antibacterial ability.

[0086] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2 in Table 2, it can be found that the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 2, which indicates that the reaction of degummed silk with DL-glyceraldehyde-3-phosphate will produce a large amount of Schiff base, which can form Schiff base silver ligands with silver acetate, and the Schiff base ligands can combine with the negative charge of the biofilm of the microorganism to rupture the biofilm, and the silver ligands can react with the functional groups such as sulfhydryl, amino, and hydroxyl on the protein by slowly releasing silver ions, thereby destroying the growth and reproduction of microorganisms, achieving the antibacterial effect, and increasing the antibacterial rate of the fiber;

[0087] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 3, which indicates that quaternary ammonium salts can destroy the cell membrane structure and promote bacterial death, thereby achieving an antibacterial effect and increasing the antibacterial rate of the fiber;

[0088] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 4, which indicates that polypyrrole has a partial antibacterial effect and increases the antibacterial rate of the fiber.

[0089] Test Example 3

[0090] Antistatic test

[0091] The YG401 fabric induction static tester was used, and the FZ / T01042-1996 "Determination of static voltage half-life of static properties of textile materials" and GB / T12703-1991 "Test methods for static electricity in textiles" were used. The high voltage applied in the experiment was 10KV, the pressure time was 30s, the discharge distance between the needle electrode and the sample was 20mm, the measurement distance between the test probe and the sample was 15mm, and each sample was tested 10 times to take the average value. The results are shown in Table 3.

[0092] Table 3

[0093] Electrostatic voltage half life Example 1 513V 1.18s Example 2 503V 1.11s Example 3 506V 1.15s Comparative Example 1 511V 1.12s Comparative Example 2 509V 1.17s Comparative Example 3 654V 4.26s Comparative Example 4 823V 10.22s

[0094] From the comparison of the experimental data in Table 3, it can be found that the antibacterial silk fabric prepared by the present invention has good antistatic ability.

[0095] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the electrostatic voltage of Examples 1, 2, 3 is larger than that of Comparative Example 3 and the half-life is longer, which shows that the loading of the foaming agent can make the material rich in pores, facilitate the subsequent pyrrole polymerization, and improve the antistatic ability of the material;

[0096] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the electrostatic voltage of Examples 1, 2, 3 is larger and the half-life is longer than that of Comparative Example 3, which shows that polypyrrole, as a conductive polymer, can improve the antistatic ability of the material.

[0097] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. An antibacterial silk fabric, characterized in that: The antibacterial silk fabric is prepared by reacting composite silk with pyrrole, and then electrostatically spinning and weaving.

2. The antibacterial silk fabric according to claim 1, characterized in that: The composite silk is prepared by loading sodium bicarbonate on the surface of quaternary ammonium modified calcium carbonate whiskers and then reacting with silver-loaded silk.

3. The antibacterial silk fabric according to claim 2, characterized in that: The silver-loaded silk is prepared by sequentially reacting degummed silk with DL-glyceraldehyde-3-phosphate, 3-hydroxypyrrole and silver acetate.

4. The antibacterial silk fabric according to claim 2, characterized in that: The quaternized modified calcium carbonate whisker is prepared by sequentially reacting trimethoxysilane with dimethylallylamine, modified calcium carbonate whisker and dibromoethane.

5. A method for preparing an antibacterial silk fabric, characterized in that: The preparation method of the antibacterial silk fabric mainly includes the following preparation steps: (1) adding the degummed silk dispersion to a DL-glyceraldehyde-3-phosphate solution of 0.3 to 0.5 times the mass of the degummed silk dispersion at a uniform speed within 8 to 10 minutes, stirring at 200 to 240 r / min for 100 to 140 minutes, filtering, washing with ethanol for 3 to 5 times, and vacuum drying at -10 to -1°C for 22 to 24 hours to obtain pre-modified silk; (2) Pre-modified silk, urea and deionized water are mixed in a mass ratio of 1:2-5:5-7, stirred at 70-80°C and 200-300 r / min for 8-10 min, heated to 80-100°C, and stirred continuously. 3-hydroxypyrrole in an amount of 0.05-0.08 times the mass of the pre-modified silk is added at a uniform rate within 50-70 min, reacted at 94-96°C for 2.5-3.5 h, and deionized water in an amount of 3-5 times the mass is added. The modified silk was prepared by mixing the modified silk, silver acetate and deionized water in a mass ratio of 1:0.5-0.7:3-5, stirring at 150-170°C and 200-300 r / min for 8-10 min, taking out, and vacuum drying at 40-60°C for 8-12 h to obtain silver-loaded silk. (3) trimethoxysilane and dimethylallylamine are mixed in a molar ratio of 1:1, chloroplatinic acid is added in an amount of 0.03 to 0.05 times the mass of trimethoxysilane, and the mixture is reacted at 60 to 70°C for 4 to 6 hours to obtain nitrogen-containing siloxane; calcium carbonate whiskers, nitrogen-containing siloxane and isopropanol are uniformly mixed in a mass ratio of 15 to 25:1:30 to 50, stirred at 85 to 95°C and 200 to 300 r / min for 5 to 7 hours, the solid is centrifuged, washed with deionized water for 3 to 5 times, and dried at 90 to 100°C for 2 to 4 hours to obtain modified calcium carbonate whiskers; (4) Mixing modified calcium carbonate whiskers, dibromoethane, ethanol and deionized water in a mass ratio of 2-4:1:1.5-2.5:7-9, stirring at 80-90°C and 200-300 r / min for 5-7 hours, filtering, washing with ethanol for 3-5 times, and drying at 50-60°C for 5-7 hours to obtain quaternized modified calcium carbonate whiskers; soaking the quaternized calcium carbonate whiskers in a saturated sodium bicarbonate solution for 30-45 seconds, taking them out, and drying them at 50-60°C for 12-14 hours to obtain foaming agent-loaded calcium carbonate whiskers; (5) Calcium carbonate whiskers carrying a foaming agent, silver-carrying silk, sodium hydride and deionized water are mixed in a mass ratio of 1:8-10:0.08-0.12:30-40, stirred at 90-110°C and 200-300 r / min for 8-12 hours, filtered, and washed with deionized water for 3-5 times to obtain composite silk; pyrrole, ethanol and deionized water are mixed in a mass ratio of 5-7:1-3:7-9, stirred at 200-300 r / min for 8-10 minutes, 0.03-0.05 times the mass of pyrrole ferric chloride is added, and stirring is continued for 20-40 seconds to obtain a pyrrole mixed solution; the composite silk is immersed in the pyrrole mixed solution for 30-50 seconds, taken out, and dried at 40-60°C for 22-26 hours to obtain modified composite silk, and the modified composite silk is electrostatically spun and woven to obtain antibacterial silk fabrics.

6. The method for preparing an antibacterial silk fabric according to claim 5, characterized in that: The degummed silk in step (1) is prepared by immersing the silk in a sodium carbonate solution having a mass fraction of 0.04% to 0.06% and boiling it for 20 to 40 minutes, taking it out, washing it with deionized water for 3 to 5 times, and then boiling it with deionized water for 20 to 40 minutes, repeating the above steps 2 to 4 times, taking out the silk, and drying it at room temperature for 20 to 24 hours.

7. The method for preparing an antibacterial silk fabric according to claim 5, characterized in that: The degummed silk dispersion in step (1) is prepared by uniformly mixing degummed silk and anhydrous ethanol in a mass ratio of 1:

1.

8. The method for preparing an antibacterial silk fabric according to claim 5, characterized in that: The DL-glyceraldehyde-3-phosphate solution in step (1) is prepared by uniformly mixing DL-glyceraldehyde-3-phosphate and anhydrous ethanol in a mass ratio of 1:

1.

9. The method for preparing an antibacterial silk fabric according to claim 5, characterized in that: The electrospinning method of step (5) is to uniformly mix the modified composite silk and hexafluoroisopropanol in a mass ratio of 1:10 to obtain an electrospinning solution; and the electrospinning solution is spun at a spinning flow rate of 1.4 to 1.6 ml / h, a spinning voltage of 14 to 16 kV, a receiving distance of 14 to 16 cm, and a collector speed of 250 to 350 r / min.